PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN LUWAK WHITE KOFFIE - -, Chusnah; Zaenuri, Ahmad (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effect of Celebrity Endorser and Brand Image on the Purchase Decision of Luwak White Koffie at Pemalang Rice Stalls. This research was conducted on Luwak White Koffie consumers, the sample used was 55 consumers. Hypothesis testing uses validity and reliability, normality test, multicollinearity test, heteroscedasticity test and autocorelas test. The analysis used is regression and correlation analysis, Determination of the t test and f test, based on the results of data analysis and discussion, partially celebrity endorser has an insignificant and positive effect on purchasing decisions with a tcount of 0.386 indicating that a significance level of 0.701> 0.05 and tcount 0.386 <t table 2.007, brand image partially significant and positive effect with tcount of 2.219 indicates that the significance level of 0.031 <0.05 and tcount of 2.219> t table 2.007. the coefficient of determination of 0.122 means the percentage contribution of the influence of variable X to Y by 12.2% while the remaining 87.8% is influenced by other variables.